Effect of addition of `carrier' DNA during transient protein expression in suspension CHO culture - Pradhan, Ketaki; Gadgil, Mugdha (Cytotechnology, 2012)
Transient protein expression using polyethyleneimine as a transfection agent is useful for the rapid production of small amounts of recombinant proteins. It is known that an increase in extracellular DNA concentration during transfection can lead to a nonlinear increase in intracellular DNA concentration. We present an approach that hypothesizes that this nonlinearity can be used to decrease the amount of plasmid required for productive transfections. Through addition of non coding `carrier' DNA to increase total DNA concentration during transfection, we report a statistically significant increase in protein (IgG) expression per unit plasmid used for transfection. This approach could be useful to increase protein yields for large scale transfections under conditions where plasmid availability is limited.
Keywords: Carrier DNA; Cell age; DNA: polyethyleneimine particle size; Medium equilibration with CO2; pH excursion; Salmon sperm DNA; Transient protein expression